2018
DOI: 10.1111/ijac.13118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sintering temperature on the morphology of ceramic hollow fibers prepared from niobium pentoxide

Abstract: Ceramic hollow fibers were prepared by the phase inversion and sintering method using niobium pentoxide (Nb 2 O 5 ) as an innovative starting material. X-ray diffraction and Raman analyses revealed the same monoclinic crystalline phase for the ceramic material, H-Nb 2 O 5 , at all the evaluated sintering temperatures. According to SEM images, the starting material was composed of polydisperse particles of irregular size and shape with sizes ranging from 12.5 to 89.7 μm. The increase in the sintering temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The mentioned morphological characteristics are due to the increasing temperatures. Consequently, the energy supplied favors the Nb 2 O 5 fiber coalescence effect, resulting in a fiber losing initial shape and introducing new particles, inducing growth until thermodynamic equilibrium [27,28]. Furthermore, according to Figure 2, samples treated at 400 • C, 500 • C, and 600 • C using a heating rate of 1 • C min −1 showed fiber-like morphology with mean diameters of 280, 130, and 84 nm, respectively.…”
Section: Optimization Of the Nb 2 O 5 Ceramic Fibersmentioning
confidence: 96%
“…The mentioned morphological characteristics are due to the increasing temperatures. Consequently, the energy supplied favors the Nb 2 O 5 fiber coalescence effect, resulting in a fiber losing initial shape and introducing new particles, inducing growth until thermodynamic equilibrium [27,28]. Furthermore, according to Figure 2, samples treated at 400 • C, 500 • C, and 600 • C using a heating rate of 1 • C min −1 showed fiber-like morphology with mean diameters of 280, 130, and 84 nm, respectively.…”
Section: Optimization Of the Nb 2 O 5 Ceramic Fibersmentioning
confidence: 96%
“…The cost of ceramic membranes is still a drawback for their widespread use in filtration processes. Some studies are reported on the use of low cost mineral materials to produce ceramic membranes at relative low sintering temperatures (Arzani et al, 2018;Bessa et al, 2017Bessa et al, , 2019Ferreira et al, 2019;Jamalludin et al, 2018;Kumar et al, 2015;Xavier et al, 2019). However, the mechanical resistance of these mineral membranes is still a concern.…”
Section: Membranementioning
confidence: 99%
“…For example, the studies regarding the application of carbon 11 , mullite and alumina 12 , kaolin, quartz, feldspar, sodium carbonate, boric acid and sodium metasilicate 13 , clay 14 , niobium 15 , calcium carbonate and titanium dioxide 16 , and alumina and activated carbon 17 in the field of membrane synthesis. Different low-cost additives are employed as banana peel powder 18 .…”
Section: Introductionmentioning
confidence: 99%